Solvation Largely Accounts for the Effect of N-Alkylation on the Properties of Nickel(II/I) and Chromium(III/II) Cyclam Complexes - Clark, Timothy; Hennemann, Matthias; van Eldik, Rudi; et al. (Inorganic Chemistry, 2002)
The source of the effect of N-alkylation on the redox properties of Ni(II/I) and Cr(III/II) cyclam complexes has been investigated using DFT calculations. The structures of the anhydrous and hydrated complexes were optimized in the gas phase, and single point calculations were performed in a polarized continuum. The main results are the following: the decrease in outer sphere solvation upon N-alkylation is the major source of the relative stabilization of the lower oxidation state complexes by the tertiary amine ligands; tertiary amine nitrogen donors are stronger σ-donors than the secondary amines, as predicted from the inductive effect of alkyls; steric strain elongates the metal-nitrogen bonds in the tertiary complexes and decreases the ligand strain energies; and the site of water binding to the complexes differs because of their different electronic structures (i.e., in the Ni complexes, the water molecules bind to the M-N-H sites, whereas in the Cr complexes they bind to the central metal cation). Outer sphere hydrogen bonding of water to the ligands in the coordination sphere lowers the ionization potentials by charge delocalization.
UnivIS-Import:2015-03-09:Pub.2002.forsch.sonder.sfb583.solvat